Permasalahan Belajar Siswa dan Strategi Sekolah Selama Pembelajaran Daring di Masa Pandemi Covid-19 - Arif Jauhari; Priyono; Cueva Syunyata R. Jauhari (Proceedings Series on Social Sciences & Humanities, 2021)
It has been more than a year of the Covid-19 pandemic, after WHO officially announced it on March 11, 2020. This pandemic has had a tremendous impact on all aspects of life, including education, where education must be carried out online. This drastic change will certainly encounter many obstacles. This study aims to determine the problems of online learning due to the Covid-19 pandemic faced by students of SMA Muhammadiyah Al Kautsar Kartasura Program Khusus and the strategies implemented by the school. This research method is a qualitative case study. Data collection techniques are observation, analysis and unstructured interviews. Observations to find the keywords of student learning problems in grade 10 science and 11 science students. Analysis to trace student conversations on social media based on the observed key words. Interviews were conducted to extract information, while the sampling technique was purposive sampling. The results showed that there were three student learning problems, namely boredom, lack of understanding of the material, and the need for internet quota. The school strategy includes, firstly relating to administration and secondly relating to the implementation of learning. The administrative strategy is carried out with flexibility in paying tuition fees and contributing to institutional development. The learning strategy is a home-school collaboration as an important component in evaluating and monitoring the teaching and learning process by online.